1973
DOI: 10.1128/jb.113.3.1144-1155.1973
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Marine Bacteria: Beneckea parahaemolytica and Beneckea alginolytica

Abstract: A collection of 169 strains, including 91 obtained from cases of gastroenteritis and 41 from localized tissue infections and infections of the eye and ear, was submitted to an extensive nutritional, physiological, and morphological characterization. The nutritional and physiological data obtained from these strains, as well as data for strains of other species of the genus Beneckea, were submitted to a numerical analysis which grouped the strains into clusters on the basis of phenotypic similarity. Strains fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…The antiserum thus obtained agglutinated the cells of V. al g i n o l y t i c u s ATCC 17749 grown on modified MOF agar medium, but not the cells grown in liquid medium. Like V. parahaemolyticus (1,4), cells of V. alginolyticus grown on agar medium possessed L-flagella, whereas cells grown in liquid medium did not, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The antiserum thus obtained agglutinated the cells of V. al g i n o l y t i c u s ATCC 17749 grown on modified MOF agar medium, but not the cells grown in liquid medium. Like V. parahaemolyticus (1,4), cells of V. alginolyticus grown on agar medium possessed L-flagella, whereas cells grown in liquid medium did not, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 80%
“…Some species of genus Vibrio have two kinds of flagella, lateral flagella (Lflagella) and polar monotrichous flagella (M-flagella) (1,4,20). Cells grown in liquid media possess only one M-flagellum on one end of each rod cell, whereas cells grown on agar media have both kinds of flagella on one cell.…”
mentioning
confidence: 99%
“…Since 84 out of 88 (95%) V. parahaemolyticus strains used in this study had peritrichous flagella in addition to a single polar flagellum when grown on solid media and Baumann et al [3] reported that the 95% of their strains of the species had peritrichous flagella, the have referred neither to the frequency of laterally flagellated strains among each Aeromonas species nor to the taxonomic position of genus Aeromonas in higher rank of classification. Buttiaux [5] regarded a strain of marine bacterium of mixed type of flagellation as a member of genus Beneckea which was defined as peritrichous rod by Campbell [6].…”
Section: Discussionmentioning
confidence: 81%
“…Although Molenda et al [26] reported the isolation of V. parahaemolyticus from patients with gastroenteritis in Maryland, they did not describe the motility and flagellation of the isolates. Baumann et al [3] reported that 125 of 132 strains (95%) of the species were peritrichous on solid media. Extending our previous work, the mode of flagellation of V. parahaemolyticus strains under various cultural conditions is presented and the significance of flagellar morphology in the taxonomy of the species is discussed.…”
mentioning
confidence: 99%
“…In 1973, Baumann et al described a group of Gram-negative, fermentative marine organisms and assigned it to group C-2 [1]. Based on the results of extensive phenotypic characterization and DNA homology experiments, Reichelt et al placed the organism in the genus Beneckea and named it Beneckea vulnifica [2].…”
Section: Introductionmentioning
confidence: 99%